- Pengaruh Ukuran Perusahaan Dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Sektor Infrastruktur Yang Terdaftar di BEI - Triyudha Akmal Fadjri; Dian Hakip Nurdiansyah (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the effect of company size and liquidity on firm value in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The samples used in this study amounted to 33 infrastructure companies, in the form of annual financial reports selected by purposive sampling method. This study uses multiple linear regression analysis models with classical assumption testing processed using the IBM SPSS V.25 program. The results of this study based on the F test show that simultaneously between independent variables have an effect of 37% on firm value and the rest is affected by other variables outside this study. Based on the t test, company size has an insignificant positive effect on firm value, while liquidity has a significant positive effect on firm value.